1994
DOI: 10.1016/1010-7940(94)90136-8
|View full text |Cite
|
Sign up to set email alerts
|

“Mold-like” calcification of the left atrium and of the pulmonary veins. Total endoatriectomy in a patient undergoing mitral valve replacement

Abstract: Mold-like left atrial calcification is a rare aspect of rheumatic mitral valvular disease. Its interest lies in the difficulty of surgical technique during interventions for valvular substitution. This is a case report in which the total excision of the calcified mold by a wide endoatriectomy was necessary in order to substitute the stenotic mitral valve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In this situation, access to the mitral valve could not be achieved and it is important to establish the extension of calcification preoperatively. Furthermore, previous reports described that an internal cast of calcium can be removed by endoatriectomy [3]. Histological evaluation of atrial wall revealed that transmural calcification penetrated and most of the myocardium disappeared in the current case.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this situation, access to the mitral valve could not be achieved and it is important to establish the extension of calcification preoperatively. Furthermore, previous reports described that an internal cast of calcium can be removed by endoatriectomy [3]. Histological evaluation of atrial wall revealed that transmural calcification penetrated and most of the myocardium disappeared in the current case.…”
Section: Discussionmentioning
confidence: 85%
“…Although calcification of the left atrium is relatively common in the setting of long-lasting rheumatic valve disease, massive calcification of the left atrium, also known as ''porcelain atrium [1],'' ''coconut atrium [2],'' or ''mold-like calcification [3],'' is a rare condition. The left atrial calcification is described as a high-density ring encircling the left atrium on chest X-ray.…”
Section: Introductionmentioning
confidence: 99%
“…During atherogenesis, endothelial dysfunction plays an important role in vascular calcification. Several investigators have demonstrated that the endothelium is a source of osteoprogenitor cells in vascular calcification [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Further inflammation during the healing process of rheumatic carditis may be involved in the pathogenesis of rheumatic heart disease.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Indeed, atrial fibrillation of many years duration is almost universal. The advanced electro anatomical remodeling of the left atrium exacerbates the hemodynamics of heart failure; ii) the consensus of other group of investigators is that left atrial calcification is the end-result of repeated and extensive rheumatic auricularis beginning with focal patches of calcification in areas of rheumatic endocardial ulceration and progression to chronic fibrotic changes with plaques of subendocardial calcium [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The incidence of atrial calcification appears to be related to the severity of the original rheumatic attack and the associated valvular damage.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation